2017
DOI: 10.1016/j.vetmic.2016.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Origin and evolution of LX4 genotype infectious bronchitis coronavirus in China

Abstract: We investigated the genomic characteristics of 110 LX4 genotype strains of infectious bronchitis viruses (IBVs) isolated between 1995 and 2005 in China. The genome of these IBVs varies in size from 27596bp to 27790bp. Most IBV strains have the typical genomic organization of other gamacoronaviruses, however, two strains lacked 3a and 5b genes as a result of a nucleotide change within the start codon in the 3a or 5b genes. Analysis of our 110 viruses revealed that recombination events may be responsible for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
(42 reference statements)
3
19
0
Order By: Relevance
“…Currently, the epitope of Group Ⅱ is widely present in IBV isolates from Asia, America, Europe, and Africa (Fig. 3A, 3B), consistent with the prevalence of the lineage GI-19, the so-called QX-type IBV, in China and worldwide (Zhao et al, 2017). Our results demonstrated that the epitope of the QX type IBV dominant in chicken flocks in China all belonged to this group of IBV strains containing 16R.…”
Section: Distribution Of Group ⅱ Strains Carrying 16r In the Epitopesupporting
confidence: 82%
“…Currently, the epitope of Group Ⅱ is widely present in IBV isolates from Asia, America, Europe, and Africa (Fig. 3A, 3B), consistent with the prevalence of the lineage GI-19, the so-called QX-type IBV, in China and worldwide (Zhao et al, 2017). Our results demonstrated that the epitope of the QX type IBV dominant in chicken flocks in China all belonged to this group of IBV strains containing 16R.…”
Section: Distribution Of Group ⅱ Strains Carrying 16r In the Epitopesupporting
confidence: 82%
“…The QX-like type IBV is a member of the LX4 group and is one of the most important IBV genotypes globally. The QX-like IBV types have been the predominant IBV type in China since 1999 (Zhao et al, 2017;Jiang et al, 2018). IBV isolates from southern China CK/CH/JS/TAHY Nasopharyngeal swabs 5/5 4/5 3/5 1/5 0/5 Cloacal swabs 4/5 5/5 3/5 3/5 3/5 Control Nasopharyngeal swabs 0/5 0/5 0/5 0/5 0/5 Cloacal swabs 0/5 0/5 0/5 0/5 0/5…”
Section: Introductionmentioning
confidence: 99%
“…More recently, phylogenetic studies have reported that-in addition to the well-established lineages/genotypes such as GI-1, GI-7, GI-13, GI-19, GI-22, and GVI-1-a number of novel IBV variants have been isolated in China (Chen et al, 2015Han et al, 2017;Xu et al, 2016Xu et al, , 2018Zhao et al, 2017). These variants have been proved to be distinct from other reference strains on the basis of genetic characteristics and phylogenetic differences in the S1 gene (Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%